Complexity of the Strategic Level and Tactical Level Disaster Management Tasks: Activity System Analysis Through the Lens of Information Behaviour - Aydın, Alperen Mehmet (Information World, 2016)
This research investigates information behaviour of the strategic and tactical level commanders’ in emergency response context. The objective of the research is to observe and analyse the information processing of the emergency staff while carrying out complex, time critical tasks in emergency settings. Task studies in the recent literature discuss laboratory cases; this research has originality in investigating the real phenomenon. Fieldwork was conducted in AKOM (Afet Kordinasyon Merkezi – Disaster Coordination Centre) and Istanbul Fire Brigade settings. Data was collected via qualitative methods such as interviews and field observations. Emergency response tasks were analysed and categorised using Byström and Jarvelin’s (1995) conceptual framework. Cultural Historical Activity Theory is used as a theoretical framework and conceptual data analysis tool. Leont’ev (1978) and Wilson’s (2006b, 2008) activity system hierarchical structure was used to deconstruct tasks and scrutinise subtasks that has supporting role in emergency response context. Findings reveal that time pressure and task complexity has significant role on emergency response decision tasks and the way of responders’ information processing. To hedge uncertainty and make effective timely decisions, tactical and strategic level commanders collaboratively share information using abstract and concrete tools such as ICT, language, mobile devices and radio. As practical implications, the results of this research shed lights onto redesign of ICT tools used during disaster times, and restructuring the disaster management organisations to facilitate effective knot working while emergency response.
Keywords: Task complexity; information behaviour; emergency response